HUBUNGAN ANTARA REGULASI EMOSI DENGAN KECENDERUNGAN PERILAKU BULLYING DI SMP NEGERI 17 BATAM TAHUN 2017 - Sauve Prilhi, Feji Sukitide; Yunita, Prasida (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
Nowadays, the raises of violent case which happen on student at school are apprehensively for teachers and parents. School should be the place for student to gain the knowledge and also place for shaping the positive character but in fact, it becomes the easiest places to expand the bullying practice. It brings anxiety for the students to enroll. This research aims to investigate the correlation of emotion regulation and bullying behavior tendency in SMPN 17 Batam. This research is using quantitative study design. The population involved 63 students. The data collecting technique is Systematic Random Sampling. The data was analyzed by using moment product correlation with SPSS program. The result of the research reveals that there is negative correalation of emotion regulation and bullying behavior tendency. It can be seen from r value -0,522 with significant point of 0,000 (p<0,01). The regulation emotion levels posses good qualification with 59 respondent (93,7%) and the low tendency of bullying behavior shows 60 respondent (95,2%). The determination coefficient resultedÂ  (r2) that the regulation of emotion only give 27,2% toward the bullying behavior tendency.